2012
DOI: 10.1227/neu.0b013e318232fdac
|View full text |Cite
|
Sign up to set email alerts
|

Limbic and Motor Function Comparison of Deep Brain Stimulation of the Zona Incerta and Subthalamic Nucleus

Abstract: We provide preliminary evidence that stimulation in or near the ZI results in maintained motor function while improving self-reported depression and anxiety in patients with bilateral STN DBS. Stimulation in or near the ZI may provide a useful programming setting for patients prone to psychiatric side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…An advantage of ILS stimulation is that 2 regions (e.g., STN and rZI) can be costimulated. With the exception of case reports, there are no large case series of ILS for the treatment of dyskinesias [20, 27-30]. The antidyskinetic effects of rZI stimulation evident in our study and reported in the literature may involve stimulation of the rZI and/or the surrounding pallidothalamic fibers.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…An advantage of ILS stimulation is that 2 regions (e.g., STN and rZI) can be costimulated. With the exception of case reports, there are no large case series of ILS for the treatment of dyskinesias [20, 27-30]. The antidyskinetic effects of rZI stimulation evident in our study and reported in the literature may involve stimulation of the rZI and/or the surrounding pallidothalamic fibers.…”
Section: Discussionmentioning
confidence: 48%
“…Retrospective studies on stimulation of sites immediately dorsal to the STN for the treatment of PD have reported clinical benefits, i.e., reduced tremor, bradykinesia, and rigidity [17, 20-25]. In the only prospective studies evaluating ZI stimulation in PD, Plaha et al [26] determined that patients with cZI or stimulation dorsomedial to the STN compared to patients with STN stimulation had greater improvement in parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventrocaudally to the ZI lies the substantia nigra [19,20] , laterally the Ci, and dorsomedially the red nucleus [21,22] . A recent study by Burrows et al [23] comparing DBS of the STN and the ZI provided similar findings resulting in sustained motor benefit with less limbic side effects, including anxiety and self-reported depression, for ZI stimulation. Furthermore, the stimulation of the cZI [18,24,25] seems to be superior compared to the stimulation of the STN in improving contralateral parkinsonism [26] .…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 69%
“…However, active electrode contacts often lie in white matter regions, including the zona incerta (ZI) and fields of Forel (FF) 7. Stimulation of the caudal ZI has been reported to be superior to stimulation of STN 8 9. To complicate the issue, the optimal stimulation site may vary by motor symptom—for example, dorsal STN for tremor, central STN for bradykinesia, and ventral STN for gait disturbance 10…”
Section: Introductionmentioning
confidence: 99%